Application of the theory of planned behavior for explaining childbearing Intentions - assessment of operationalization and measurement - Mynarska, Monika (Studia Psychologica: Theoria et praxis, 2012)
The aim of the article is to evaluate how well the theory of planned behavior (TPB, Ajzen, 1991) has been operationalized within the Generation and Gender Programme. In this project, the TPB has been applied as a theoretical framework for investigating childbearing intentions. According to the model, childbearing intentions are determined by: attitudes towards having children, subjective norms concerning childbearing and perceived behavioral control. Scales to measure these variables have been introduced into the Generation and Gender Survey (GGS) that has been administered to thousands of respondents in Europe - almost 7 thousand individuals responded to the questions on childbearing intentions in Poland. The analyses conducted on the Polish data indicate that the reliability of the scales to measure attitudes, norms and perceived behavioral control is high. Nevertheless, several signihcant problems with their validity have been identihed. In particular, the scale of the perceived behavioral control does not provide valid results and should not be used to explain childbearing intentions.